PERANCANGAN SISTEM INFORMASI TPQ AISYAH MAULIDA HASANAH BERBASIS WEBSITE - Afif Amirudin; Muhamad Azrino Gustalika (LPPM Universitas Putera Batam, 2023)
The development of the increasingly advanced digital world makes the speed of information also faster and more complex. However, with all the facilities available, the use of information technology is still a little applied in local communities. The learning documentation process at TPQ Aisyah Maulidah Hasanah still uses the conventional method, where students and parents of students can only see learning outcomes through paper media. The recording of monthly contribution payments also still uses a notebook which has the potential to lose data if a lost book is replaced or a book is lost. Information technology can be used to help TPQ Aisyah Maulidah Hasanah and parents of students so that data recording is safer through a website-based information system which is expected to facilitate the processing and receipt of information by TPQ managers and parents of students regarding recording the development of student achievements and payment of dues. Using the waterfall method and the Laravel framework, this website-based information system is expected to streamline the process of recording information related to the development of students' achievements and to minimize the potential for data loss